The greedy python - Buckley, Richard; Carle, Eric (Natick, MA : Picture Book Studio USA : Distributed by Alphabet Press, 1985)
A greedy python eats to excess, finally eating himself.
Keywords: Pythons -- Fiction; Snakes -- Fiction; Food habits -- Fiction; Stories in rhyme